Reconstruction of Economic Law Regulations: Strengthening Buy Now Pay Later (BNPL) Governance in the Digital Economy Era - Fatahuddin Aziz Siregar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The development of the digital economy has driven the transformation of financial services through the Buy Now Pay Later (BNPL) innovation that offers easy access to financing for the public. Behind its rapid growth, BNPL services also raise various legal issues, including unclear electronic contract clauses, weak consumer protection, misuse of personal data, irresponsible lending practices, and the lack of harmonization of legal arrangements that govern the BNPL ecosystem in Indonesia. This condition shows the need to reconstruct economic law regulations in order to be able to accommodate the development of financial technology while ensuring legal certainty and justice for all parties. This study aims to analyze the weaknesses of economic law regulations in BNPL governance and formulate a regulatory reconstruction model that is adaptive to the development of the digital economy. The research uses normative legal methods with laws and regulations, conceptual, and comparative approaches. Primary legal materials in the form of regulations regarding consumer protection, electronic transactions, personal data protection, and the financial services sector are analyzed qualitatively through interpretation, synchronization, and legal construction techniques. The results of the study show that BNPL regulations are still sectoral, not yet integrating consumer protection, personal data governance, transparency of credit scoring algorithms, and comprehensive cross-sector supervision. This research offers a reconstruction model of economic law regulations that focuses on regulatory harmonization, strengthening the principle of responsible lending, operator accountability, personal data protection, transparency of electronic contracts, and risk-based supervision mechanisms to realize fair, adaptive, and sustainable BNPL governance in the digital economy era.